Force control in hydraulic actuators through proportional relief valve (2018)
With the formulation of Pascal’s principle, an important work has been developed in fl uid power and control. The variables most used in this fi eld are: speed, position and force; there is suffi cient literature on this subject, especially when related to proportional four-way /three state valves Control de fuerza en actuadores hidráulicos mediante válvula proporcional de alivio1 Force control in hydraulic actuators through proportional relief valve Controle da força em atuadores hidráulicos mediante válvula proporcional de alívio D.A. Echeverry, F.J. Henao Fecha recibido: junio 7 de 2017 - Aceptado: junio 29 de 2017 as final control element. These valves behave very well for speed and position, but when it comes to a fi ne force control, proportional relief valves are required. The present article shows the force control in hydraulic actuators by means of a proportional relief valve, performing its characterization and behavior experimentally. Furthermore, a scheme integrating the hydraulic elements, data acquisition and system intercommunication is generated through an interface between the control system and the actuators, with the purpose of regulating the force, which consists on a pre-established load.